Assessing the 3D structural behavior of RC library buildings with/without non-structural elements considering shake table tests and 3D numerical analyses - Karalar, Memduh; Çavuşlu, Murat; Ozturk, Hakan; Mert, Necati; Ahmad, Mahmood; Sabri, Mohanad Muayad Sabri (Frontiers in Materials, 2022)
In this study, it is aimed to reveal how anchored and unanchored non-structural elements (NEs) in the reinforcement concrete (RC) library structures change the earthquake behaviors of these structures. A library structure is selected for three-dimensional (3D) analyses. First, seismic shake table tests are performed for selected NEs modeled with/without anchorage to the structure. Thanks to these seismic tests, the largest seismic displacement values that occurred during 10 different earthquakes on each anchored and unanchored NE are acquired. Then, special seismic loads (e.g. high bookcase loads, heavy table loads) of anchored and unanchored NEs are calculated taking into account ASCE/SEI 7-16 seismic design code and the 2018 New Turkish earthquake code. Seismic spring values of NEs are calculated using obtained seismic forces and maximum seismic displacements for the NEs. Then, these spring values are applied to the base of the NEs in the 3D model of the structure and 10 different earthquake analyzes are conducted for the library structures with anchored and unanchored NEs. According to the numerical results, the seismic effects of NEs on earthquake behavior of RC library structures are evaluated for two different seismic design codes in detail and it is concluded that NEs should not be neglected while modeling and analyzing RC library structures. Moreover, it is clearly understood that anchored or unanchored NEs have differently seismic effects on the 3D earthquake behavior of library structures.